Emergence of high-risk ST595 and ST640 clones of carbapenem-resistant Serratia marcescens: insights from genomic and virulence profiling during a nosocomial epidemic - Zhang, Yan; Cao, Tong; Zheng, Jie; Meng, Lingning; Gao, Shuo; Shen, Han; Zhou, Wanqing; Cao, Xiaoli (Frontiers in Microbiology, 2025)
ObjectiveCarbapenem-resistant Serratia marcescens (CRSM) poses a significant threat in hospital settings due to its potential for persistence and transmission. This study aims to elucidate the virulence landscape of carbapenem-resistant Serratia marcescens (CRSM) during a hospital outbreak and to identify high-risk clones with enhanced persistence and transmission potential.MethodsA total of 52 CRSM clinical isolates collected during a nosocomial outbreak were subjected to whole-genome sequencing (WGS) for comprehensive analysis of virulence factor (VF) profiles, sequence types (STs), and phylogenetic relationships. Based on genomic clustering, representative isolates were selected for in vitro phenotypic assays, including bacterial growth kinetics, biofilm formation, and serum bactericidal activity.ResultsAll the CRSM carried blaKPC-2 (52/52), other carbapenemases detected included blaNDM-1 (n = 3), blaOXA-23 (n = 6), and blaOXA-66 (n = 6). In addition, the majority of them harbored blaSRT-1 (48/52), blaCTX-M-14 (42/52) and blaTEM-1B (25/52). Two major epidemic clones were identified: ST595 (n = 25) and ST640 (n = 17), indicating clonal expansion during the outbreak. All isolates carried a conserved set of core VFs, including shlA, shlB, hlyA, and multiple genes associated with motility and iron acquisition. Additional accessory VFs, such as plcN (n = 33) and fliF (n = 20), were variably distributed. Phenotypic characterization revealed that specific isolates, notably SM60, simultaneously exhibited accelerated growth, robust biofilm formation, and marked serum resistance—a combination of traits that may drive both environmental persistence and immune evasion in hospital settings.ConclusionThis study provides the first integrated genomic and phenotypic characterization of CRSM during a documented hospital outbreak, highlighting ST595 and ST640 as high-risk clones with distinct virulence signatures. The convergence of rapid growth, biofilm capacity, and serum resistance in select isolates underscores their potential role in prolonged colonization and nosocomial spread. These findings emphasize the urgent need for genomic surveillance and targeted infection control strategies to curb the dissemination of emerging CRSM clones.